FIRE PREVENTION AND HANDLING TRAINING FOR RESIDENTS OF BATU MERAH VILLAGE, SIRIMAU DISTRICT, AMBON CITY - Ruspanah, Rendi; Lefteuw, Theresya; Lapodi, Abd Rijali (Jurnal Abdisci, 2025)
Fires can occur unexpectedly, even if you have been careful to use appliances that produce fires in the house, some of the sources of fire are electrical short circuits, gas stoves, burning garbage, cigarette butts and candles when the lights go out. The purpose of the training in community service is to provide knowledge about the causes of fires and their preventive measures. Participants involved in the training included students of the Public Health Department of STIKes Maluku Husada, Instructors from the Ambon City Fire Service Tribe and residents of Batu Merah Village, Sirimau District, Ambon City. Training techniques with material presentation, practice and review of results. The implementation method is by identifying problems that occur in objects, determining the priority scale of improvement and providing problem solving and feedback in the form of result evaluation. The implementation of training can provide knowledge about the factors that cause fires at home, so that it can encourage public awareness of the importance of preventive measures to avoid fires. The conclusion of the training in community service is that it can provide knowledge about the factors that cause fires and know preventive measures to minimize the occurrence of fires and can encourage concern in fire prevention in the community.